2008
DOI: 10.1111/j.1365-2672.2007.03711.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of methods for counting surviving biofilm cells adhering to a polyvinyl chloride surface exposed to chlorine or drying

Abstract: Aim:  To compare techniques for assessing biofilm populations previously subjected, or not, to inimical treatment by chlorine or drying. Methods and Results:  Four sonication treatments and swabbing were compared on Salmonella Typhimurium or Pseudomonas fluorescens biofilms grown on polyvinyl chloride (PVC). The apparatuses emitting the highest ultrasound energy were the most efficient except on Salm. Typhimurium biofilms subjected to drying: a lethal effect, leading to an underestimation of at least 1·5 log (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 26 publications
(62 reference statements)
1
19
0
3
Order By: Relevance
“…We hypothesized that increase in k w observed at higher velocity could be attributed to organic matter release from pipe wall which accelerated the rate of chlorine consumption. This hypothesis is supported by other studies that reported higher cell counts in the biofilm formed on PVC as compared to copper or polyethylene pipe surfaces [12][13][14] . Another study reported that the organic matter released is directly proportional to the shear stress exerted on the walls as water flows in the pipe which become constant after attaining a certain velocity 15 .…”
Section: Wall Reaction Ratesupporting
confidence: 84%
“…We hypothesized that increase in k w observed at higher velocity could be attributed to organic matter release from pipe wall which accelerated the rate of chlorine consumption. This hypothesis is supported by other studies that reported higher cell counts in the biofilm formed on PVC as compared to copper or polyethylene pipe surfaces [12][13][14] . Another study reported that the organic matter released is directly proportional to the shear stress exerted on the walls as water flows in the pipe which become constant after attaining a certain velocity 15 .…”
Section: Wall Reaction Ratesupporting
confidence: 84%
“…4). This observation suggests that the bead vortexing procedure and/or the conventional plating technique used in this study could underestimate the attached microbial population on SS coupons and thus the actual risk of contaminated surfaces (1). It has also been suggested that in order to survive under adverse environmental conditions, many food-borne pathogens enter a viable but nonculturable state (i.e., a dormant state) (51) in which they maintain metabolic activity and pathogenicity but cannot be cultured by common laboratory methods (39).…”
Section: Discussionmentioning
confidence: 93%
“…Sonication is well established as a method to clean surfaces and aid in the removal of biofilms from many types of material surfaces (17)(18)(19). Sonication can be applied to remove adhered biofilms while maintaining cell viability, if employed properly (14,20,21). Biofilm-associated bacteria grown on polyvinyl chloride and stainless steel slides had higher recovery rates when placed in a sonication bath, in comparison with sampling with cotton swabs (21).…”
Section: Importancementioning
confidence: 99%
“…Sonication can be applied to remove adhered biofilms while maintaining cell viability, if employed properly (14,20,21). Biofilm-associated bacteria grown on polyvinyl chloride and stainless steel slides had higher recovery rates when placed in a sonication bath, in comparison with sampling with cotton swabs (21). Direct and indirect contact of stainless steel coupons (SSCs), inoculated with Listeria monocytogenes, with a sonicating toothbrush yielded significantly higher recovery rates (59% and 61%, respectively) than did the Dacron-tipped swab tested (21%) (20).…”
Section: Importancementioning
confidence: 99%